1983
DOI: 10.1123/jsp.5.4.419
|View full text |Cite
|
Sign up to set email alerts
|

What is Learned in Mental Practice of Motor Skills: A Test of the Cognitive-Motor Hypothesis

Abstract: To test the cognitive-motor hypothesis, mental practice effects were examined using two tasks judged to differ only in the degree of motor involvement. Male college students (N = 60) learned either the high motor task or the low motor task under conditions of physical practice (PP), mental practice (MP), or no practice (NP). On each task, the PP group received 12 physical trials; the MP group received one physical, nine mental, then two physical trials; and the NP group received one physical trial, a rest peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
3
16
0
2
Order By: Relevance
“…Novice subjects benefitted more from mental practice on cognitive tasks than on physical tasks. This result is consistent with Ryan and Simons' (1983) argument that if an experienced individual has already learned the component motor skills of a physical task then mental practice may be sufficient to enhance performance without additional physical practice and feedback. But for noLices, who have not formed an approximation of the skill, the symbolic rehearsal provided by mental practice may not be sufficient to guide performance.…”
Section: Mental Practicesupporting
confidence: 91%
“…Novice subjects benefitted more from mental practice on cognitive tasks than on physical tasks. This result is consistent with Ryan and Simons' (1983) argument that if an experienced individual has already learned the component motor skills of a physical task then mental practice may be sufficient to enhance performance without additional physical practice and feedback. But for noLices, who have not formed an approximation of the skill, the symbolic rehearsal provided by mental practice may not be sufficient to guide performance.…”
Section: Mental Practicesupporting
confidence: 91%
“…It has been found that the higher the level of cognitive involvement in the task, the greater the benefit from mental rehearsal [10,46]. Ryan and Simons altered the amount of motor involvement in the tasks and found that on a high motor task mental practice was not significantly superior to no practice while on a low motor task, mental practice and physical practice groups were insignificantly different, with both significantly superior to the no practice group [62]. Smyth found only insignificant effects of the amount of symbolic content [56J.…”
Section: Type Of Skillmentioning
confidence: 99%
“…Esses mecanismos cognitivos podem facilitar os meios para alcance da meta da habilidade-alvo, bem como consolidar estratégias de detecção e correção de erros em estágios mais avançados 20 . A PM, também, permite ativar os músculos que seriam responsáveis pela execução real do movimento.…”
Section: Discussionunclassified
“…A PMsegundo uma abordagem neuromuscular -provoca ativação muscular e reforça representações motoras da habilidade-alvo [15][16][17] . De acordo com uma abordagem cognitiva, durante a PM o aprendiz focaliza a atenção para aspectos relevantes da habilidade-alvo e fortalece mecanismos de processamento de informação, isto é, identifi cação e percepção do estímulo e posterior seleção, programação e execução da resposta motora [18][19][20][21] . O ato de imaginar durante a PM pode envolver tipos distintos de mentalização 9,13,[22][23][24][25] , ou perspectivas de mentalização, as quais são o foco do presente trabalho.…”
unclassified